5x-3=3(x+6)

Simple and best practice solution for 5x-3=3(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=3(x+6) equation:


Simplifying
5x + -3 = 3(x + 6)

Reorder the terms:
-3 + 5x = 3(x + 6)

Reorder the terms:
-3 + 5x = 3(6 + x)
-3 + 5x = (6 * 3 + x * 3)
-3 + 5x = (18 + 3x)

Solving
-3 + 5x = 18 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3 + 5x + -3x = 18 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-3 + 2x = 18 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + 2x = 18 + 0
-3 + 2x = 18

Add '3' to each side of the equation.
-3 + 3 + 2x = 18 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = 18 + 3
2x = 18 + 3

Combine like terms: 18 + 3 = 21
2x = 21

Divide each side by '2'.
x = 10.5

Simplifying
x = 10.5

See similar equations:

| 3/2=18÷x | | 6a-5b=1 | | X^2+3x-12+-6=0 | | 3x+4-9-4x=12 | | v=4/3*3.14*(21)3 | | 4x=2(48-4) | | h/6-1= | | x(4x-6)=(4x+7)(x-5) | | 5X1/14 | | 2x+x-24=90 | | X-1=4x-22 | | 4x=2(48-3) | | 15x-3x+2(x+4)=48 | | z^2+3z=-1 | | 13-4t+5t=-5-2 | | 11/4y-3/12y=10 | | (13+a)+14= | | 7x+3x-2=-3(-11-x) | | 3k+6=9 | | 2x+11x+5=8 | | 11=5x^2 | | 3(3k+5)-13k+6+4= | | 2x+7x-1=-2(-10-x) | | 2.45+0.15+1.55= | | 3b+5=5(b+1) | | 3(2x-4)-5(x-1)-4(3x-5)+5=-4+6(x+2)-3(x+2)-3(4x+1)+3(x-4)-1 | | 3x-6x=6x+1 | | x+14223x=119425 | | 6x-5x+3=6 | | -720=-48 | | 92837373772626-4-5-56-778999092992929-99-9-0-00-0-0-0+1222627272= | | 38=-16x^2+48x+2 |

Equations solver categories